Lipid-rich extract from Mexican avocado (Persea americana var. drymifolia) induces apoptosis and modulates the inflammatory response in Caco-2 human colon cancer cells. (January 2020) - Lara-Márquez, Mónica; Báez-Magaña, Marisol; Raymundo-Ramos, Cristina; Spagnuolo, Paul A.; Macías-Rodríguez, Lourdes; Salgado-Garciglia, Rafael; Ochoa-Zarzosa, Alejandra; López-Meza, Joel E.
Graphical abstract: Highlights: Lipid extract from avocado seed are cytotoxic to Caco-2 cells. Lipid extract from avocado induces apoptosis on Caco-2 cells. LEAS stimulates secretion of IL-6, IL-8 and IL-10 but inhibits IL-1β in Caco-2 cells. Avocado is a source of functional food products for cancer control. Abstract: Colorectal cancer (CRC) is the third most common type of cancer worldwide. Chemotherapy used in CRC patients has severe side effects. As an alternative, the search to identify natural compounds increases the opportunity to select therapeutics. In this work, the cytotoxic effect of a lipid extract (LEAS) from Mexican native avocado seed ( Persea americana var . drymifolia) on colon cancer cells Caco-2 was determined. LEAS was cytotoxic towards Caco-2 cells (IC50 = 28 µg/ml), inducing apoptosis through the activation of caspases 8 and 9. Also, LEAS induced loss of membrane mitochondrial potential, inhibited fatty acid oxidation and increased the superoxide production and mitochondrial ROS. Furthermore, LEAS stimulated secretion of cytokines IL-6 ( 500%), IL-8 ( 400%) and IL-10 ( 150%); whereas IL-1β secretion was inhibited ( 50%). The results suggest that LEAS induces apoptosis on Caco-2 cells, indicating that avocado is a source of functional food products that can reduce the risk for development of cancer.